Exploring safety at mass gathering events through the lens of three different stakeholders - Hutton, Alison; Robertson, Martin; Ranse, Jamie (Frontiers in Public Health, 2025)
IntroductionThe work here reviews the role of those with responsibility in managing people and their safety at Mass Gathering Events (MGE); event managers, police, and medical personnel. This paper comes at a time when there is an acute need for appropriate application of psychosocial understanding and biophysical knowledge for the safe management of the social environment of MGE, and the broader community. Safety has become increasingly significant in the vocabulary of researchers, managers, funding agencies and public bodies involved in the provision of mass gathering events.MethodFocus groups were used to gain insight into MGE safety through the lens of three different groups. Through prioritising safety at mass gathering events, organisers enhance the quality of the event, protect individual and promote the long-term success of the event. Questions were centred on their understanding of safety at events, based on their experiences in MGEs.ResultsParticipants in this study identified many risks to event safety, including lack of risk assessment, communication, lack of ownership of risk and poor planning. Even though these risks were similar, each participant group identified their own perspective with their own ways of managing them.DiscussionThe work proposes that all event stakeholders should focus on the interests of both the audience and the broader event community, with the goal of working together to foster a safe, supportive, and trusting environment. Building trust in the context of mass gathering events brings forward an opportunity for new orientation strategies. A framework for developing personal skills and community resilience for mass gathering events is shown.